1999
DOI: 10.1152/ajplung.1999.276.3.l412
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human airway smooth muscle proliferation by type 3 phosphodiesterase inhibition

Abstract: Elevation in cell cAMP content can inhibit mitogenic signaling in cultured human airway smooth muscle (HASM) cells. We studied the effects of the type 3-selective phosphodiesterase inhibitor siguazodan, the type 4-selective phosphodiesterase inhibitor rolipram, and the nonselective inhibitor 3-isobutyl-1-methylxanthine (IBMX) on proliferation of cultured HASM cells. At concentrations selective for the type 3 phosphodiesterase isoform, siguazodan inhibited both [3H]thymidine incorporation (IC50 2 μM) and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…PTX inhibits phosphodiesterase activity, resulting in an increase in cAMP (18). An increase in cAMP can inhibit proliferation (29). cAMP inhibited the activation of Rap1 and reduced Akt phosphorylation (30).…”
Section: Discussionmentioning
confidence: 99%
“…PTX inhibits phosphodiesterase activity, resulting in an increase in cAMP (18). An increase in cAMP can inhibit proliferation (29). cAMP inhibited the activation of Rap1 and reduced Akt phosphorylation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-␣ is one cytokine implicated in the exacerbation of asthma (3,6,10), and recent clinical studies raise hope that targeted therapy against TNF-␣ may improve asthma symptoms (6). Cyclic AMP is an important second messenger involved in the regulation of the contractile state, proliferation (8,25,34), migration (19), and cytokine secretory abilities (1) of airway smooth muscle cells. Previous studies in human airway smooth muscle cells have shown that cytokines, such as TNF-␣ and IL-1␤, directly influence cellular cAMP levels by "sensitizing" the activities of adenylyl cyclase enzymes (9,29), but the intracellular signaling pathways for the modification of adenylyl cyclase activity are unknown.…”
mentioning
confidence: 99%
“…However, the work presented by Kumara a et al [17] reported that pathogenesis of BHR could be independent on the inflammation and can be present in IL-4 and IL-13 knock-out animals. Inhalation of IL-5 in experiment leads to the increase of the eosinophils and onset of BHR [18]. IL-9 produced by T lymphocytes, eosinophils and mast cells stimulates in turn proliferation of T lymphocytes, increases production of IgE in B lymphocytes and supports proliferation and differentiation of mast cells.…”
Section: The Role Of Nervous System In Pathogenesis Of Bhrmentioning
confidence: 99%
“…Another selective inhibitor of PDE3 siguazodan inhibited allergen induced bronchoconstriction in sensitized guinea pigs [48]. The same drug in vitro significantly reduced proliferation of airway smooth muscle [49]. Administration of selective PDE3 inhibitors olprinon [50] and MKS492 [51] induced significant bronchodilatation with minimal systemic side effects.…”
Section: Selective Phosphodiesterase Inhibitors (Pde)mentioning
confidence: 99%